Investigating Engine Lecturers’ Achievement for Academic Quality Improvement at Politeknik Ilmu Pelayaran (PIP) Makassar - Limbong, Sunarlia; Sunusi, Muhammad Syafril; Tandibura, Frans; Rasinan, Djusniati; Chandra, Ade (JED (Jurnal Etika Demokrasi), 2024)
Improving the quality of education cannot be done partially, but must be comprehensive and sustainable. This research aimed to investigate engine lecturers’ achievement for academic quality improvement at Politeknik Ilmu Pelayaran (PIP) Makassar. This research used a qualitative approach with a case study research type and descriptive using primary and secondary data from ten informants in the engineering study program. The research results show that the achievement of lecturers significantly impacts the enhancement of academic quality. Those are essential components of the education and teaching process, contributing to research and scientific advancement. Lecturer achievement include teaching effectiveness, research output, and contribution to the academic community. Hence, a lecturer must perform at their best to generate professional and high-quality outcomes. The academic excellence achieved by lecturers is evident in the quality of graduates and the success of alumni, which indicates the education's quality. In conclusion that lecturers' accomplishments have a substantial influence on improving academic quality through teaching methods, research and scientific progress, teaching efficiency, research outcomes, and involvement in the academic achievement that is demonstrated through the quality of graduates.